2014
DOI: 10.1016/j.smim.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of IL-6 in the tumor microenvironment

Abstract: Within the tumor microenvironment, IL-6 signaling is generally considered a malevolent player, assuming a dark visage that promotes tumor progression. Chronic IL-6 signaling is linked to tumorigenesis in numerous mouse models as well as in human disease. IL-6 acts intrinsically on tumor cells through numerous downstream mediators to support cancer cell proliferation, survival, and metastatic dissemination. Moreover, IL-6 can act extrinsically on other cells within the complex tumor microenvironment to sustain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
464
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(505 citation statements)
references
References 84 publications
8
464
3
1
Order By: Relevance
“…34 By delaying the DLI and allowing full engraftment of BM-derived IL-6 2/2 cells following allo-BMT, we were able to significantly decrease CAR-associated GVHD. Consistent with the complexities of IL-6 production in tumor immunology, 44 our finding that loss of IL-6-producing capacity in BM-derived cells was sufficient to prevent GVHD provides insights into the potential source of IL-6 in the setting of CRS and suggests that, although CAR T cells can produce IL-6, they may not be the primary source. Finally, complete absence of IL-6 from BM, recipient, and CAR T cells did not prevent leukemic control in both syngeneic and allogeneic settings, suggesting that IL-6 may not be essential for CAR T-cell efficacy.…”
Section: Discussionsupporting
confidence: 71%
“…34 By delaying the DLI and allowing full engraftment of BM-derived IL-6 2/2 cells following allo-BMT, we were able to significantly decrease CAR-associated GVHD. Consistent with the complexities of IL-6 production in tumor immunology, 44 our finding that loss of IL-6-producing capacity in BM-derived cells was sufficient to prevent GVHD provides insights into the potential source of IL-6 in the setting of CRS and suggests that, although CAR T cells can produce IL-6, they may not be the primary source. Finally, complete absence of IL-6 from BM, recipient, and CAR T cells did not prevent leukemic control in both syngeneic and allogeneic settings, suggesting that IL-6 may not be essential for CAR T-cell efficacy.…”
Section: Discussionsupporting
confidence: 71%
“…Aside from the factors secreted by HSCs and LSECs, tumor cells are stimulated by KCs present in the liver sinusoids, which are known to promote tumor progression at multiple levels, including promoting adhesion, proliferation, immune tolerance and angiogenesis (40). Ligand binding to ICAM-1 activates KC secretion of IL-6 (41), which induces cell proliferation via the STAT3 pathway, and stimulates the degradation of surrounding ECM via increased secretion of matrix metalloproteinases (MMPs) (101). IL-6 has been also implicated in the differentiation of human monocytes to M2 macrophages (102), a mechanism that probably also occurs in liver and is related to tumor progression (103).…”
Section: Tumor Cell Extravasation: Opening the Liver's Doors To Invadmentioning
confidence: 99%
“…IL-6 mediates several important physiological functions, including the control of the acute-phase inflammatory response and the support of cell growth and survival (24). Several studies have suggested that IL-6 is a key mediator of the development of metastatic potential in cancer cells (25,26). Previous studies have indicated that IL-6 promotes the initial steps of cancer metastasis, potentially by upregulating MMP-9 through the PI3K/Akt signal pathway (27,28), and it has been demonstrated that IL-6 induces EMT through the expression of molecular markers (29,30).…”
Section: Discussionmentioning
confidence: 99%